Atherosclerosis severity is not affected by a deficiency in IL‐33/ST2 signaling. Issue 3 (10th May 2015) - Martin, Praxedis; Palmer, Gaby; Rodriguez, Emiliana; Woldt, Estelle; Mean, Isabelle; James, Richard W.; Smith, Dirk E.; Kwak, Brenda R.; Gabay, Cem
Abstract Interleukin (IL)‐33 is a cytokine of the IL‐1 family, which signals through the ST2 receptor. Previous work demonstrated that the systemic administration of recombinant IL‐33 reduces the development of atherosclerosis in apolipoprotein E‐deficient (ApoE−/−) mice by inducing a Th1‐to‐Th2 shift. The objective of our study was to examine the role of endogenous IL‐33 and ST2 in atherosclerosis. ApoE−/−, IL‐33−/−ApoE−/−, and ST2−/−ApoE−/− mice were fed with a cholesterol‐rich diet for 10 weeks. Additionally, a group of ApoE−/− mice was injected with a neutralizing anti‐ST2 or an isotype control antibody during the period of the cholesterol‐rich diet. Atherosclerotic lesion development was measured by Oil Red O staining in the thoracic‐abdominal aorta and the aortic sinus. There were no significant differences in the lipid‐staining area of IL‐33−/−ApoE−/−, ST2−/−ApoE−/−, or anti‐ST2 antibody‐treated ApoE−/− mice, compared to ApoE−/− controls. The absence of IL‐33 signaling had no major and consistent impact on the Th1/Th2 cytokine responses in the supernatant of in vitro‐stimulated lymph node cells. In summary, deficiency of the endogenously produced IL‐33 and its receptor ST2 does not impact the development of atherosclerosis in ApoE‐deficient mice.